2007
DOI: 10.1128/jcm.00100-07
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Load at Matched Anatomic Sites: Implications for Screening Strategies

Abstract: Urethral and endocervical swabs and self-collected vaginal swabs (SCVSs) and urine specimens are all used as samples for diagnosis of urogenital infection with Chlamydia trachomatis. We have now determined chlamydial organism load in matched specimens from different anatomic sites and examined its relation to clinical signs and symptoms in men and women. Organism load was measured with assays based on the ligase chain reaction or real-time PCR analysis. The mean organism loads in 58 infected men were 1,200 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 31 publications
6
91
2
1
Order By: Relevance
“…Given that salpingitis is a necessary condition for TFI (6,32,42), it seems reasonable to regard the CT+++ group, which is observed in cases only, as representing a causal mechanism linked to CTrelated TFI. It is tempting to attribute this to a greater inflammatory response possibly due to a higher infectious load in those who develop TFI, as has been observed at the lower genital tract and in PID (43,44). The 28.0% (6.9, 50.0) estimate of PEF based on the CT+++ distribution alone can be regarded as a lower bound because it ignores the excess CT++ observed in the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Given that salpingitis is a necessary condition for TFI (6,32,42), it seems reasonable to regard the CT+++ group, which is observed in cases only, as representing a causal mechanism linked to CTrelated TFI. It is tempting to attribute this to a greater inflammatory response possibly due to a higher infectious load in those who develop TFI, as has been observed at the lower genital tract and in PID (43,44). The 28.0% (6.9, 50.0) estimate of PEF based on the CT+++ distribution alone can be regarded as a lower bound because it ignores the excess CT++ observed in the cases.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by the results of the present study, as demonstrated by the similar PCR positivity rates for the matched CS and VS specimens (Table 1). For women infected with C. trachomatis, CS specimens contain the highest organism load, followed in decreasing order by VS specimens, urethral swabs, and first-void urine (23). However, despite their lower organism load than CS specimens, VS specimens are gaining acceptance as the specimen of choice for screening and diagnostic purposes because their collection is noninvasive, easier, and less expensive and their chlamydial load is sufficient for most tests to maintain sensitivity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Urine specimens have lower sensitivity than vaginal and endocervical specimens. [32][33][34] Hence, false negative results for urogenital infection could lead to an overestimate in the number of women who are positive only for rectal infection. Fourth, utilizing clinic billing records to identify patients for the retrospective review may raise a concern about selection bias.…”
Section: Discussionmentioning
confidence: 99%